Impact of virtual reality experiences on destination image and visit intentions: the moderating effects of immersion, destination familiarity and sickness - Anaya-Sánchez, Rafael; Rejón-Guardia, Francisco; Molinillo-Jiménez, Sebastián (Emerald Insight, 2024)
The aims of this study are to explore how the experience of “visiting” a destination in a virtual reality (VR) technology environment influences destination image and visit intentions and to evaluate the moderating effects of the immersion level of the technology, destination familiarity and VR sickness.
Keywords: Realidad virtual- Turismo; Tecnología educativa; Turismo; Virtual reality; Destination image; Familiarity; Tourism destination; Customer experience; Google Earth; Immersive technology; Visit intentions; Sickness